E-comics: Pictorial Learning Media to Train Students' Viewing Skills - Michael Berger; Guri Michael; Nash Christoph (Journal Emerging Technologies in Education, 2023)
Background. Nowadays, education requires ways to improve the quality of students. In improving and developing the quality of students, teachers must innovate in making learning media, one of which is learning media in the form of e-comic media. Purpose. this is to find out how the benefits of e-comics in learning. Method. using quantitative methods, data obtained through interviews and distributing questionnaires to students by utilizing the google form. Results. explained that learning media using e-comics can improve student learning outcomes. From the results of the interviews, it was obtained that these students felt an attraction and were motivated in learning by using e-comics. Students feel that learning by using e-comic media, grades and learning outcomes are increasing. e-comics is also one of the learning media that is easily understood by students. Conclusion. explained that this e-comic learning media really helps teachers to see students' skills in learning. e-comics is one of the learning media that is easily understood and liked by students as well as an effective learning media to use in learning.